2011
DOI: 10.1096/fj.11-182089
|View full text |Cite
|
Sign up to set email alerts
|

Annexin A1 regulates neutrophil clearance by macrophages in the mouse bone marrow

Abstract: Under homeostatic conditions, a proportion of senescent CXCR4hi neutrophils home from the circulation back to the bone marrow, where they are phagocytosed by bone marrow macrophages. In this study, we have identified an unexpected role for the anti-inflammatory molecule annexin A1 (AnxA1) as a critical regulator of this process. We first observed that AnxA1−/− mice have significantly increased neutrophil numbers in their bone marrow while having normal levels of GM and G colony-forming units, monocytes, and ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
71
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 79 publications
(79 citation statements)
references
References 48 publications
7
71
0
1
Order By: Relevance
“…Many mediators can accelerate the clearance of apoptotic granulocytes mediated by macrophages, including AnxA1, IL-10, and proresolution lipids (2). The increased expression of GILZ and AnxA1 (15) observed during the resolution phase of inflammation may contribute to increase the efferocytic capacity of macrophages, an effect already demonstrated for AnxA1 (17,40).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Many mediators can accelerate the clearance of apoptotic granulocytes mediated by macrophages, including AnxA1, IL-10, and proresolution lipids (2). The increased expression of GILZ and AnxA1 (15) observed during the resolution phase of inflammation may contribute to increase the efferocytic capacity of macrophages, an effect already demonstrated for AnxA1 (17,40).…”
Section: Discussionmentioning
confidence: 86%
“…Indeed, AnxA1 limits initial steps of inflammation, specifically the recruitment of leukocytes and generation of proinflammatory mediators. AnxA1 also acts on the resolution phase of inflammation by inducing apoptosis of neutrophils (14,15) and increasing efferocytosis by macrophages (16,17). Importantly, AnxA1 production and activities are involved in proresolution effects of GCs (18) and histone deacetylase inhibitors (19).…”
Section: R Esolution Of Inflammation Is An Active and Continuousmentioning
confidence: 99%
“…In response, the epithelium has evolved a remarkable capacity to efficiently reseal the barrier defects. Such important reparative responses are modulated by mucosal mediators, such as anti-inflammatory protein ANXA1 (60)(61)(62)(63). The beneficial effects of ANXA1 are exerted by a unique N-terminal peptide that is released by proteolysis from the full-length protein (2,13,14,64).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, macrophages in ANXA1-defi cient mice have reduced capacity to clear apoptotic bodies (31) . Notably, Tzelepis et al (35) reported that these mice are highly susceptible to Mycobacterium tuberculosis, and that ANXA1 expression is signifi cantly downregulated in infected dendritic cells, suggesting that suppression of ANXA1 is a critical mechanism for immune evasion by Mycobacterium tuberculosis.…”
Section: Anxa1 Expressionmentioning
confidence: 99%